1995
DOI: 10.1002/ptr.2650090414
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activities of extracts of Daniellia oliveri (Rolfe) Hutch. and Dalz. (Leguminosae)

Abstract: Extracts of the stem bark of Danielliu oliuen' using hexane, ethyl acetate and methanol were tested for analgesic, antipyretic and antiinflammatory activities. The hexane extract exhibited a dose related analgesic activity whilst the methanolic extract was active in the induced inflammatory condition. The ethyl acetate extract was relatively inactive and none of the extracts showed any antipyretic activity. Metabolic cage studies showed that a 70% ethanolic extract of the bark caused significant decreases in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Ethanol extract of the bark caused significant decreases in body weight, food intake, urine and stool out put of rats. This extract also exhibited a competitive antagonism on histamine-induced contractions of guinea-pig ileum and a non-competitive inhibition of acetyl choline-induced contraction of the frog rectum abdominal muscle (Onwukaeme, 1995). The methanol extracts of bark and leaf have neuromuscular blocking properties.…”
Section: Biologcal Activity and Toxicologymentioning
confidence: 97%
“…Ethanol extract of the bark caused significant decreases in body weight, food intake, urine and stool out put of rats. This extract also exhibited a competitive antagonism on histamine-induced contractions of guinea-pig ileum and a non-competitive inhibition of acetyl choline-induced contraction of the frog rectum abdominal muscle (Onwukaeme, 1995). The methanol extracts of bark and leaf have neuromuscular blocking properties.…”
Section: Biologcal Activity and Toxicologymentioning
confidence: 97%
“…According to Sawadogo et al, Ben A. Chindo [13,14] these components are responsible for the anti-inflammatory properties of plant extracts. Previous works have proven the pharmacological activity of Daniellia oliveri [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Yaya et al, 2016 demonstrated the antiinflammatory activity of the leaf aqueous extract of Daniellia oliveri [7]. Moreover Onwukaeme ND, 1995 showed the anti-inflammatory and analgesic effects of the stem bark of this plant [8]. In this study, the investigations are focused on demonstrating the anti-edematous and analgesic properties of the methanolic extract and the fraction of the stem barks of Daniellia oliveri to provide scientific data for further studies.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A decoction of the leaves and bark of D. oliveri is used for the treatment of gastrointestinal complaint, headaches, and as a mouthwash to treat toothache. 11 D. oliveri has been reported to have, among other properties, antinociceptive, [12][13][14] cytotoxic, 15 hepatoprotective and antioxidant, 16 anti-hyperglycemic, 17 and anthelmintic activities. 18,19 In addition, the antioxidant activity of the seed oil, 11 Ethnobotanically, the stem bark of D. ogea is taken in Senegal as an aphrodisiac.…”
mentioning
confidence: 99%